18.8k views
0 votes
Which of the following Expressions is equivalent to 5(2x + 1)-4 show your work to justify your response test at least one value of x to check your answer

A. 10 x -3 B. 7 x -3
C. 10 x + 1 D. 7x + 1

1 Answer

6 votes

Lets Simplify Step by Step:

5(2x + 1) - 4

Distribute:

(5)(2x) + (5)(1) + -4

10x + 5 + -4

Combine Like Terms:

10x + 5 + -4

(10x) + (5 + -4)

10x + 1

Hence, Letter Choice, (C); 10x + 1 ===> 5(2x + 1) - 4

CHECK:

5(2x + 1) - 4 ====> 10x + 1 ===> True for all x ===> Both Sides Equal.

Steps:

5(2x + 1 ) - 4 = 10x + 1

Expand:

5(2x + 1 ) - 4 ====> 10x + 1

10x + 1 =====> 10x + 1

Subtract 1 from both sides:

10x + 1 - 1 =====> 10x + 1 - 1

Simplify:

10x = 10x

Subtract 10x form both sides:

10x - 10x = 10x - 10x

Simplify:

0 = 0

Therefore, when checked, 5(2x + 1 ) - 4 ===> 10x + 1, Which makes Both Sides Equal; True for All " x "

Have a great day : )

User Gigaxel
by
5.8k points